HALAL INDUSTRY AND CERTIFICATION IN DISGUISE: Is It Faith Implementation or Economic Ploy in Indonesia’s Legal Framework? - Rahmatullah, Rahmatullah; Haryono, Slamet; Ardi, Muh Zaitun; Syaefullah, Syaefullah; Saputra, Viant Anggi (Fakultas Syariah, 2025)
The halal industry in Indonesia has experienced rapid growth, but the implementation of halal certification still encounters issues. The main challenges include misuse of the halal logo, limited enforcement of the Law No. 33 of 2014 concerning Halal Product Guarantee and its regulatory mechanisms, and inadequate consumer protection at both the national and international levels. This situation has sparked debate over whether micro-enterprises seek halal certification for religious reasons or primarily in response to market pressures, raising broader concerns about the decline of spiritual values in contemporary halal practices. This study uses a critical qualitative method with an interdisciplinary approach, combining insights from Islamic economics, Islamic studies, and the sociology of religion, while the maqāṣid al-syarī‘ah framework and Islamic economic law serve as the theoretical basis. Findings indicate that halal certification serves both religious and economic purposes, with the two dimensions reinforcing each other. While Halal certification represents moral responsibility and a value of worship, it is also embedded in a global production and distribution system governed by legal frameworks and market logic. The study concludes that the most significant challenge lies in the trade-off between spiritual orientation and economic interests, which can be addressed through more effective Halal certification management. Furthermore, this study argues that strengthening the enforcement of Law No. 33 of 2014 and adopting the proposed Participatory Halal Governance theory can inform halal governance policy reform, improve consumer protection, provide legal certainty, and strengthen Indonesia's competitiveness in the global halal economy. Industri halal di Indonesia telah mengalami pertumbuhan yang pesat, namun implementasi sertifikasi Halal masih menghadapi berbagai masalah. Tantangan utama meliputi penyalahgunaan logo Halal, penegakan hukum yang terbatas terhadap Undang-Undang No. 33 Tahun 2014 Tentang Jaminan Produk Halal dan mekanisme regulasinya, serta perlindungan konsumen yang tidak memadai baik di tingkat nasional maupun internasional. Situasi ini memicu perdebatan tentang apakah usaha mikro mencari sertifikasi Halal berdasarkan keyakinan agama atau terutama sebagai respons terhadap tekanan pasar, yang menimbulkan kekhawatiran lebih luas tentang penurunan nilai-nilai spiritual dalam praktik halal kontemporer. Studi ini menggunakan metode kualitatif kritis dengan pendekatan interdisipliner, menggabungkan wawasan dari ekonomi Islam, studi Islam, dan sosiologi agama. Kerangka maqāṣid al-syarī‘ah dan hukum ekonomi Islam menjadi dasar teoretis. Temuan menunjukkan bahwa sertifikasi Halal berfungsi sebagai alat keagamaan dan ekonomi, dengan kedua dimensi saling memperkuat. Sertifikasi Halal mewakili tanggung jawab moral dan unsur ibadah, tapi juga tertanam dalam sistem produksi dan distribusi global yang diatur oleh kerangka hukum dan logika pasar. Studi ini menyimpulkan bahwa tantangan terbesar terletak pada menyeimbangkan orientasi spiritual dan kepentingan ekonomi melalui tata kelola sertifikasi Halal yang lebih efektif. Selain itu, studi ini berargumen bahwa memperkuat penegakan Undang-Undang No. 33 Tahun 2014 dan mengadopsi Teori Tata Kelola Halal Partisipatif yang kelola Sertifikasi Halal, meningkatkan perlindungan konsumen, memberikan kepastian hukum, dan memperkuat daya saing Indonesia dalam ekonomi halal global.